PANDANGAN HUKUM ISLAM TERHADAP SEORANG ISTRI YANG BEKERJA MENAFKAHI KELUARGA - Uwandi, Uwandi (STAI Darul Qalam Tangerang, 2025)
This study aims to examine the view of Islamic law on the phenomenon of wives who work as the main breadwinner in the family, as well as its impact on domestic harmony. This phenomenon is increasingly prevalent in line with increasing economic needs and shifting gender roles in modern society. This study uses a qualitative approach with a case study method in Gebang Sukamulya Village, Tangerang, Banten. The results show that in Islam there is no prohibition for wives to work as long as they are in accordance with the sharia. However, the dynamics of these roles can affect relationships in the household which, if not properly managed, can cause tension. In conclusion, Islam provides space for women to play an active role in the family economy while maintaining the values of responsibility and harmony.